Journalistic Ethics In The Post-Truth Era: Challenges And Implications In Mass Media - Laeis, Zuhdiar; Naryoso, Agus; Nurayyan, Amanda D; Sakinah KP, Dianti (Jurnal Spektrum Komunikasi, 2025)
The post-truth era is characterized by the dominance of emotions and subjective opinions over objective facts, blurring the lines between reality and perception. This phenomenon poses serious challenges to journalistic integrity and ethical principles in journalistic work. This study aims to systematically review the scientific literature discussing ethical dilemmas, external pressures, and deviations in journalistic integrity between 2019 and 2024. By applying a systematic review approach and integrating three main theoretical frameworks, this study identifies the dynamics of roles, morality, and information interference that affect the quality of journalists' work. The analysis demonstrates the importance of ethical courage, institutional strengthening, and ongoing ethical literacy as the foundation for maintaining integrity amidst disinformation. This paper also proposes the Triadic Model of Integrity as a framework for further analysis and critical reflection on the realities of contemporary journalistic practice.